2006
DOI: 10.1111/j.1471-4159.2006.03936.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptide neuroprotection through specific interaction with brain tubulin

Abstract: This study aimed to identify the neuronal target for the potent neuroprotective peptide NAP. When added to pheochromocytoma cells (neuronal model), NAP was found in the intracellular milieu and was co-localized with microtubules. NAP induced neurite outgrowth and protected primary neurons against microtubule-associated ZnCl 2 toxicity. Rapid microtubule reorganization into distinct microtubules ensued after NAP addition to both pheochromocytoma cells and primary cerebral cortical neurons, but not to fibrobalst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
110
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 57 publications
4
110
0
Order By: Relevance
“…To date, two tubulin-interacting agents, NAP and paclitaxel have been shown to reduce tau pathology in vivo. Paclitaxel was shown to diminish the NAP-tubulin interaction in vitro (Divinski et al, 2006), suggesting that these two agents work, in part, through a related mechanism. Although paclitaxel is a nonselective tubulin-interacting agent and is associated with severe adverse effects in humans, NAP exhibits preferential interaction with neuronal tubulin (Divinski et al, 2006) as well as brain bioavailability (Gozes et al, 2000(Gozes et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, two tubulin-interacting agents, NAP and paclitaxel have been shown to reduce tau pathology in vivo. Paclitaxel was shown to diminish the NAP-tubulin interaction in vitro (Divinski et al, 2006), suggesting that these two agents work, in part, through a related mechanism. Although paclitaxel is a nonselective tubulin-interacting agent and is associated with severe adverse effects in humans, NAP exhibits preferential interaction with neuronal tubulin (Divinski et al, 2006) as well as brain bioavailability (Gozes et al, 2000(Gozes et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…The octapeptide NAPVSIPQ (NAP) preferentially interacts with neuronal and glial tubulin, promotes microtubule assembly, influences microtubule dynamics in postmitotic cells, and reduces phosphorylated tau in vitro at femtomolar concentrations (Divinski et al, , 2006Gozes and Divinski, 2004). Peripheral administration of NAP has shown significant efficacy in various in vivo models and penetration into the brain at therapeutic levels (Gozes et al, 2005).…”
mentioning
confidence: 99%
“…Structure-activity studies identified a short peptide sequence in ADNP, NAP (NAPVSIPQ), that mimics the neuroprotective activity of the parent protein and crosses the blood brain barrier after systemic or intranasal administra-tion (Gozes et al, 2005a). Importantly, NAP interacts with tubulin and enhances microtubule assembly to increase neurite outgrowth and to specifically protect neurons and glial cells against severe toxicities (Divinski et al, 2006). In vitro, NAP was found to reduce tau hyperphosphorylation ) that has been associated with neurodegeneration/tauopathy and cognitive decline in vivo (Modrego, 2006).…”
mentioning
confidence: 99%
“…This peptide is believed to interact with neuronspecific bIII-tubulin (Divinski et al 2006;Matsuoka et al 2007), and intranasal administration of NAP to Tg mice that develop both Ab and tau pathology resulted in a reduction of hyperphosphorylated tau and diminution of Ab peptide levels. Similarly, a recent study showed that intranasal dosing of NAP to Tg mice expressing mutated tau also led to a reduction of tau phosphorylation (Shiryaev et al 2009).…”
Section: Compensation For Tau Loss-of-functionmentioning
confidence: 99%